Pendampingan Muallaf untuk Meningkatkan Pemahaman Agama dan Kemandirian Ekonomi di Kecamatan Girimulyo Kabupaten Kulun Progo - Imadudin, Ihsan Sidiq (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
The mentoring program for Muslim converts in Girimulyo District, Kulon Progo Regency, Special Region of Yogyakarta Province emerged from the need for ongoing religious guidance and economic empowerment. This study aims to describe the implementation of mentoring, which includes basic Islamic education and economic skills development for Muslim converts. A qualitative approach was used to explore participants' experiences, the types of support provided, and the changes they experienced. The results indicate that structured mentoring can improve religious understanding, build self-confidence, and open up better economic opportunities. These findings underscore the importance of programs that combine spiritual guidance and economic empowerment to improve the quality of life for Muslim converts at the local level.